PENINGKATAN HASIL BELAJAR SISWA KELAS XI SMA NEGERI 4 AMBON PADA MATERI IRISAN KERUCUT DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF MELALUI MEDIA PEMBELAJARAN CAI (COMPUTER ASSISTED INSTRUCTION) BERBANTUAN SOFTWARE GEOGEBRA - Lekitoo, John; Moma, La; Ngilawajan, Darma Andreas (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2018)
Theaims of this study is to improve the learning outcomes of grade XI students of SMA Negeri4 Ambon in cone slice material using a cooperative learning model through CAI (Computer Assisted Instruction) learning media  assisted by geogebrasoftware. Students divided into small groups (3 groups) with each groups consist of 5-6 students who have varied abilities. The results showed that by using the cooperative learning model throughlearning media CAI (Computer Assisted Instruction)assisted by geogebrasoftware, there was an increase in the learning outcomes of grade XI MIA students at SMA Negeri 4 Ambon